Transit-Oriented Data: The Importance of Data and Coordination to Transit-Oriented Urban Transformation - Ray, Rosalie Singerman; Garrick, Norman; Atkinson-Palombo, Carol (Frontiers in Sustainable Cities, 2022)
Planners, academics, and policy-makers recognize the importance of transit-oriented development (TOD) in building resilient and sustainable cities, though implementation has not always lived up to expectations. TOD is an example of a network governance problem as actors from multiple organizations (developers, lenders, and multiple government agencies at different scales), each with their own goals, must come together for an extended time to manage risk and implement a single solution. Less well studied is the importance of spatial data and state-level coordination to this task, both in identifying sites and in developing policies at the state or regional level to encourage and prioritize TOD in certain areas. This study uses a 1+n case study model, focusing on a primary case (Connecticut’s TOD efforts) but using the experience of other states (MassGIS and the New Jersey Transit Villages program) to inform the primary case. Working from interviews with Connecticut stakeholders and participant observation in TOD policy development, the study explores the coordination and governance challenges surrounding state intervention as well as the role that Connecticut’s weak state geospatial data play in the efforts to develop TOD projects. Connecticut was until recently one of only five states without a state geographic information officer, making it a “black swan” case that can illuminate the perhaps unseen role that strong spatial data infrastructures play in other states’ policymaking. Moreover, the comparison between New Jersey’s Transit Villages Program and Connecticut’s efforts signal that more work is needed to manage the difficult paradigm shift toward state support of TOD.